The effectiveness of problem-based learning model to increase the students’ critical thinking skills - Daud Dakabesi; Isana Supiah Yosephine Luoise (Intelektual Pustaka Media Utama, 2019)
The previous research result showed that the learning model based on the investigation could increase the students’ critical thinking skills. The aim of this research was to measure the effectiveness of the using of problem-based learning model to increase the students’ critical thinking skills. The research design was quasi-experiment by using post-test only design. The population of this research was the eleventh grade students of science which contained 124 students of SMAN 6 and SMAN 7 Kupang that were chosen randomly. The treatment that was given in this research was problem-based learning model for the experiment class and conventional model for the control class whereas the given materials were the reaction rate. The instrument that was used in this research previously validated by two experts of theory and material. The result of this research showed that the students who studied in experiment class had different critical thinking skills better that the students who studied using conventional model.